2002
DOI: 10.1073/pnas.232308999
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiles associated with aging and middle age-onset caloric restriction in mouse hearts

Abstract: To provide a global analysis of gene expression in the aging heart, we monitored the expression of 9,977 genes simultaneously in 5-and 30-month-old male B6C3F1 mice by using high-density oligonucleotide microarrays and several statistical techniques. Aging was associated with transcriptional alterations consistent with a metabolic shift from fatty acid to carbohydrate metabolism, increased expression of extracellular matrix genes, and reduced protein synthesis. Caloric restriction (CR) started at 14 months of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
218
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 289 publications
(239 citation statements)
references
References 66 publications
18
218
1
1
Order By: Relevance
“…In other organisms including mouse, the opposite correlation between fat storage and life span was also observed (44). The up-regulation of a TAG lipase and consequently down-regulation of TAG in ctbp-1(ok498) may reflect a possible change in energy utilization, which was implicated in caloric restriction animals and long-lived Snell dwarf mouse (45,46). Thus, the increased expression of LIPS-7 in the ctbp-1 mutant may contribute to life span extension by directly impacting energy metabolism and/or by changing lipid composition, membrane fluidity and signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…In other organisms including mouse, the opposite correlation between fat storage and life span was also observed (44). The up-regulation of a TAG lipase and consequently down-regulation of TAG in ctbp-1(ok498) may reflect a possible change in energy utilization, which was implicated in caloric restriction animals and long-lived Snell dwarf mouse (45,46). Thus, the increased expression of LIPS-7 in the ctbp-1 mutant may contribute to life span extension by directly impacting energy metabolism and/or by changing lipid composition, membrane fluidity and signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…In that study, CR did not alter the effect of aging on gadd153 expression. By using a similar approach to examine age-related changes in gene expression in mouse heart, it was recently reported that gadd153 expression is not affected by aging but is reduced Ͼ3-fold by CR (49). Such disparate findings point to important organ/cell type-specific differences in the aging process of mammals.…”
Section: Ros Contribute To Increasing Gadd153 Levels By Egf Treatmentmentioning
confidence: 99%
“…The intracellular availability of fatty acids would be an important factor here. Indeed, several genes involved in fatty acid transport to the mitochondria are downregulated in aging (28). These novel findings signify that fatty acids may play an important regulatory role in reducing oxidative stress generation and, thus, the process of physiological aging.…”
Section: Hypothesismentioning
confidence: 84%